Persuasive Communication Strategy Implementation In Attracting Consumer Interest - Muchammad Ali Imron Rosadi; Leonard Adrie Manafe (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Berkah Mulya Jaya (BMJ) is a business engaged in the workshop, spare parts for carts and tricycles. In addition to producing workshop products, the company also receives services such as lathes, welding, cutting and ironing. To maintain market share in current conditions, companies must maintain business continuity by implementing a persuasive communication strategy. Implementing this strategy will impact consumer interest in buying the company's products and good business relationships. This research aims to determine whether the company has effectively implemented persuasive communication in attracting consumer interest. The research model used is a qualitative method with a case study approach. Data collection techniques used interviews and direct observation of eight informants, namely business owners and company consumers. The results show that BMJ has implemented a persuasive communication strategy to attract consumers' interest. The strategy tools used in persuasive communication are commitment, social proof, liking, and authority.